Stylistic Analysis of Surah An-Naas: A Study of Semantic Aspects and Word Choice - Syarafi, M. Rifqi Sulthon Sharhan; Akmal, Moch. Izzuddin (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
From a stylistic perspective, this article examines the linguistic beauty and depth of meaning in Surah An-Naas, with an emphasis on word choice and semantic aspects. This short surah, which is frequently recited in daily life, actually contains several layers of profound meaning when analyzed linguistically. Using a qualitative approach and text analysis, this study investigates how the use of words such as rabb, malik, and ilah—which may appear similar—actually creates nuanced and complementary layers of protection. Furthermore, the analysis of word structure, repetition, and vocabulary reveals that, in addition to functioning as a prayer for protection, this surah also conveys a theological message about acknowledging God’s absolute authority. According to the analysis, the vocabulary choices in Surah An-Naas have a psychological effect of tranquility and confidence on the listener, while its semantic elements contribute to the unity of meaning. Therefore, the stylistic analysis of this surah not only enhances our linguistic understanding of the sacred text but also provides an opportunity to appreciate the linguistic miracle of the Qur’an.